THE IMPACT OF RAIL BASED INFRASTRUCTURE DEVELOPMENT ON LAND VALUES (CASE STUDY OF LRT JAKARTA: PEGANGSAAN DUA STATION â VELODROME STATION) - Juansyah Abdulrahman, Yopi
Increasing accessibility through by building rail-based transportation infrastructure is one of the factors that can affect changes in land values. Land values in an area can experience an increase in land value and a decrease in land value. An increase in land value can increase economic growth in an area so that it can increase government revenue and a decrease in land value can be caused by external impacts such as noise that can be detrimental to the community. Therefore, it is necessary to identify changes in land values for spatial planning of an area. The purpose of this study is to investigate the effect of rail-based infrastructure development on land values within the scope of the LRT Jakarta area from Pegangsaan Dua Station to Velodrome Station because there has been no specific research in the LRT Jakarta area. The data collection method used in this study involved gathering secondary data obtained from the Regional Revenue Agency (Bapenda) of DKI Jakarta Province and the official website of the DKI Jakarta provincial government. The analysis method used in this research include spatial-statistic analysis, hedonic pricing model using ordinary least squares (OLS) regression, and difference in differences analysis. The result of this study indicate that the development of rail-based infrastructure have a significant effect on the land values in its vicinity, both for an 800-meter buffer and for a 2- kilometer buffer. The changes in land values are influenced by independent variables, which for the 800-meter buffer include land use, distance to the nearest park/green space, distance to the nearest shopping center, distance to the nearest educational facility, and distance to the nearest bus terminal. For the 2-kilometer buffer, the influencing variables includes population density, distance to the nearest hospital, distance to the nearest shopping center, and distance to the nearest TransJakarta bus stop. This study concludes that the development of rail-based infrastructure has a significant effect on land values in the surrounding area. Therefore, the recomendation of this study relates to the need improve good accessibility to the Jakarta LRT Station.